Hotel or rented flat: A profile of purchasers of accommodation services in Warsaw - Dziedzic, Ewa (Turyzm/Tourism, 2023)
The spreading of short-term flat rentals has brought about changes in the accommodation market, often seen as a threat to traditional accommodation providers. This is particularly true in large cities which have a considerable accommodation capacity and also a large stock of flats. The aim is to indicate to what extent short-term rentals are influencing the tourist accommodation market in Warsaw. The idea behind the study is the assumption that the differences revealed between those using hotels or such flats will provide an answer to the question of the influence of the latter on Warsaw»s tourist market. Such information should be useful in the marketing activities of interested parties and in the policies of the city authorities. Analysis of the data from a survey carried out in 2021 using the CHAID decision tree indicates that the choice of accommodation type was mainly determined by situational variables. The only statistically significant demographic predictor relates to a greater interest in flats among those aged up to 34 years old. Planned expenditure per person per overnight stay proved to be a statistically significant predictor only for non-residents of Poland, with the cut-off amount set higher than the median interval for this segment. Flats were more often chosen by people travelling in a larger party or alone and those planning to stay longer than four nights, thus looking for a different offer than that of traditional city hotels.